The effectiveness of movement control order (MCO) phases implementation in Malaysia / Hezlin Aryani Abd Rahman, Muhammad Akram bin Rahman, 'Ain Najihah Rozaimi and Irfan Bihar Zulnahar - Abd Rahman, Hezlin Aryani; Rahman, Muhammad Akram; Rozaimi, Ain Najihah; Zulnazar, Irfan Bihar (Universiti Teknologi MARA, 2022)
The COVID-19 cases have taken its strike since December 2019 in Wuhan, China and then has spread to other countries. Malaysia was not excluded from this pandemic, in which the first case of COVID-19 was discovered on 25th January 2020. The disease has caused a pandemic outbreak ever since, driving many countries to close international gateways and implement lockdowns and many studies have been trying to model and forecast the rising number of COVID-19 cases worldwide. This study aimed to prove the effectiveness of Movement Control Order (MCO) phases implemented in Malaysia. From 8 MCO phases implemented in Malaysia, 5 of the MCO phases were taken into consideration for this study. Line plots were used to observed the pattern, increasing (+) or decreasing (-) number of cases for each MCO implementation. The before and after trends for each phase were recorded and tabulated. Using the Wilcoxon Signed-rank test with Binomial probability calculation showed the p-value=0.001< α=0.05 obtained. Hence, supported the hypothesis that MCO implementation reduces the number of positive cases in Malaysia. In conclusion, the implementation of lockdown would 'flatten the curve' of the daily COVID-19 cases, resulting in better control over the spread of the COVID-19 virus in Malaysia.